Internet pornography and relationship quality: A longitudinal study of within and between partner effects of adjustment, sexual satisfaction and sexually explicit internet material among newly-weds. (April 2015) - Muusses, Linda D.; Kerkhof, Peter; Finkenauer, Catrin
Highlights: Husband's SEIM use reciprocally negatively affected their relationship adjustment. Sexual satisfaction of husband's predicted a decrease in their wives' use of SEIM. Wives' use of SEIM did not affect their husbands' sexual satisfaction. Abstract: Several studies have established a negative relation between the use of sexually explicit Internet material (SEIM) and relationship quality. While most studies imply SEIM use decreases relationship quality, the opposite might also be true: lower relationship quality might increase people's SEIM use. This article aims to shed light on the directionality of the relation between SEIM use and relationship quality among married couples. We used prospective dyadic data to examine the short- and long-term relation between SEIM use, sexual satisfaction, and relationship adjustment among adult SEIM users and their partners. The results showed that, among husbands, adjustment and SEIM use are negatively and reciprocally related. Also, sexual satisfaction among husbands predicted a decrease in their wives' SEIM one year later, while wives' SEIM did not affect their husbands' sexual satisfaction. The findings have important implications for theories on the link between relationship quality and SEIM use.